Acute hepatic porphyria - classification, diagnosis and treatment - Czekaj, Aleksandra; Ruszel, Kinga; Dubel, Robert; Dubel, Julia; Namroży, Natalia (Journal of Education, Health and Sport, 2022)
Porphyrias belong to the group of inherited metabolic diseases. Each of the four types of acute hepatic porphyria is caused by a different mutation in the gene of an enzyme involved in the heme biosynthetic pathway. The literature distinguishes between: Acute Intermittent Porphyria (AIP), Hereditary Coproporphyria (HCP), Variegate Porphyria (VP) and Aminolevulinic Dehydratic ADP (ADP) deficiency. -deficient Porphyria). Deficiency of individual enzymes leads to ineffective heme production and accumulation of neurotoxic intermediates - the so-called porphyrins. Two excess metabolites are of major importance in diagnostics - ALA (amionolevulinic acid) and PBG (porphobilinogen). In most cases, the activity of the less functional enzyme is so high that the disease never becomes apparent (latent form). Excessive accumulation of porphyrin precursors is associated with exposure to porphyrinogenic factors, leading to a seizure whose symptoms are closely related to autonomic, peripheral neuropathy, and accompanying neuropsychiatric disorders. In diagnostics, particular attention should be paid to the circumstances of the symptoms and the history of the patient’s disease, which often includes numerous episodes of unexplained abdominal pain, which was so severe that it forced the patient to report to emergency departments. A severe attack of porphyria is a medical emergency and requires hospitalization. Failure to diagnose or properly treat it may result in flaccid tetraplegia, respiratory failure, brain edema, coma, and sudden circulation detention.